Emerging Advances of Cell‐Free Systems toward Artificial Cells. Issue 10 (20th August 2020) - Zhu, Yi; Guo, Xiaocui; Liu, Jinqiao; Li, Feng; Yang, Dayong
Abstract: Artificial cells that mimic the architectural and functional characteristics of living cells not only shed light on the physical principle of life but also facilitate development in the areas such as cell engineering and biomedicine. Cell‐free systems carry out the central dogma that refers to the transcription and translation in the absence of living cells, offering a simplified and controllable platform to study cellular biological processes and design principle. Many efforts have been devoted to construct artificial cells by using cell‐free systems with mimicking cellular structures and characteristics, such as molecular crowding, compartments, gene noise, network, dynamic behavior, and cell communication. Here, the recent emerging advances of cell‐free system toward artificial cells are summarized and discussed. It is notable that this area involves multidisciplinary fields such as material chemistry, nanotechnology, and molecular biology. Although there are still much difficulties and challenges for bottom‐up designing systems with desirable properties for cells, it is firmly believed that with the development of synthetic biology, artificial cells based on the cell‐free systems will provide more possibilities to mimic the complex structures and behaviors of cells. Abstract : Cell‐free systems carry out transcription and translation in vitro, offering a simplified and controllable platform to study cellular principle. There has been an increasing drive toward the utilization of cell‐free systems to construct artificial cells with mimicking cellular characteristics such as crowding, compartments, noise, network, dynamic behavior, and communication, thus facilitating the development in the areas cell engineering and biomedicine.